Collision avoidance in multi-robot systems through cluttered environments - Denker, A.; Uyguro?lu, Mustafa K. (Institute of Electrical and Electronics Engineers Inc., 1990)
The research reported here addresses itself to the automatic collision-free path planning of robots sharing the same workspace in the presence of obstacles. The work has been carried-out upon the underlying assumption that robots are with known kinematics and the environment can be modelled in advance. The strategy for collision avoidance is based on the determination of an avoidance trajectory, which is implemented initially for collision detection and subsequently for avoidance. An explicit representation of free work space, provides the first step. As a second step, the relative position of the moving arm, with respect to another moving body which enters into this free work space, is depicted by two sets of parameters which characterize the translational and rotational movements of the arms, a collision controller is introduced for collision avodiance within the boundaries of the free work space. In application of this approach different cases of practical importance are considered, which incorporate a combination of different number of moving robot arms along with arbitrary obstacles. © 1991 IEEE.
1990 IEEE International Workshop on Intelligent Motion Control, IMC 1990 -- 1990-08-20 through 1990-08-22 -- Istanbul -- 146924
Keywords: Intelligent robots; Motion planning; Multipurpose robots; Robot programming; Cluttered environments; Collision detection; Collision-free path-planning; Collisions avoidance; Explicit representation; Moving body; Multi-robot systems; Relative positions; Rotational movement; Work space; Collision avoidance